Increasing trends of overweight and obesity in treatment-naive people living with HIV in Shenzhen from 2014 to 2020: an emerging health concern - Li, Tianze; Sun, Liqin; He, Yun; Zhou, Yang; Xu, Liumei; Zhao, Fang; Hu, Dongsheng; Wang, Hui; Lu, Hongzhou; Liu, Jiaye (Frontiers in Public Health, 2023)
Background: With the early initiation of antiretroviral therapy (ART) in China, the demographics of treatment-naïve people living with HIV (PLWH) are moving closer to those of general population, which is characterized by a gradual increase in metabolic indicators. However, the epidemic trends of overweight and obesity in treatment-naïve PLWH ready to initiate ART have not yet been investigated over the past decade.A cross-sectional study was conducted to include 12,135 consecutive treatment-naïve PLWH ready to initiate ART in Shenzhen with data retrieved from the China National Free Antiretroviral Treatment Program database from 2014 to 2020. The chi-square test was used to examine the trends of overweight and obesity between age groups and multivariate logistic regression was used to identify the association between overweight and obesity and hyperglycemia and dyslipidemia.Results: During the 7-year study period, 12,135 treatment-naïve PLWH ready to initiate ART were included, including 1,836 (14.5%) who had overweight and 388 (3.01%) obesity. The prevalence rose from 11.4% to 17.3% (χ 2 = 29.75, P < 0.01) for overweight and 2.2% to 5.9% for obesity (χ 2 = 16.76, P = 0.01) from 2014 to 2020, respectively. The annual prevalence of overweight was the highest in the age group of >35 years compared to the prevalence in other age groups during 2014-2020. Compared with those who were not overweight and obese, PLWH who were overweight or obese were more likely to have hyperglycemia (aOR 1.84, 95%CI: 1.37-2.49 for overweight and